Does oxygen affect ageing mechanisms of Pinus densiflora seeds? A matter of cytoplasmic physical state. (27th January 2022) - Gerna, Davide; Ballesteros, Daniel; Arc, Erwann; Stöggl, Wolfgang; Seal, Charlotte E; Marami-Zonouz, Nicki; Na, Chae Sun; Kranner, Ilse; Roach, Thomas
Abstract : Seed ageing mechanisms depend on the physical state of the cytoplasm. Oxygen enhanced lipid peroxidation and accelerated seed viability loss when cytoplasm was glassy, but not when fluid. Abstract: During desiccation, the cytoplasm of orthodox seeds solidifies into an intracellular glass with highly restricted diffusion and molecular mobility. Temperature and water content govern seed ageing rates, while oxygen (O2 ) can promote deteriorative reactions. However, whether the cytoplasmic physical state affects involvement of O2 in seed ageing remains unresolved. We aged Pinus densiflora seeds by controlled deterioration (CD) at 45 °C and distinct relative humidity (RH), resulting in cells with a glassy (11% and 30% RH) or fluid (60% and 80% RH) cytoplasm. Hypoxic conditions (0.4% O2 ) during CD delayed seed deterioration, lipid peroxidation, and decline of antioxidants (glutathione, α-tocopherol, and γ-tocopherol), but only when the cytoplasm was glassy. In contrast, when the cytoplasm was fluid, seeds deteriorated at the same rate regardless of O2 availability, while being associated with limited lipid peroxidation, detoxification of lipid peroxide products, substantial loss of glutathione, and resumption of glutathione synthesis. Changes in metabolite profiles provided evidence of other O2 -independent enzymatic reactions in a fluid cytoplasm, including aldo-keto reductase and glutamate decarboxylase activities. Biochemical profiles of seeds stored under seed bank conditions resembled those obtained after CD regimes that maintained a glassy cytoplasm. Overall, O2 contributed more to seed ageing when the cytoplasm was glassy, rather than fluid.